Dynamic cortical participation during bilateral, cyclical ankle movements: effects of aging - Yoshida, Takashi (Sci Rep, 2017)
The precise role of the human primary motor cortex in walking is unknown. Our previous study showed that the primary motor cortex may contribute to specific requirements of walking (i.e., maintaining a constant movement frequency and bilaterally coordinating the feet). Because aging can impair (i) the ability to fulfill the aforementioned requirements and (ii) corticomuscular communication, we hypothesized that aging would impair the motoneuronal recruitment by the primary motor cortex during bilateral cyclical movements. Here, we used corticomuscular coherence (i.e., coherence between the primary motor cortex and the active muscles) to examine whether corticomuscular communication is affected in older individuals during cyclical movements that shared some functional requirements with walking. Fifteen young men and 9 older men performed cyclical, anti-phasic dorsiflexion and plantarflexion of the feet while seated. Coherence between the midline primary motor cortex and contracting leg muscles cyclically increased in both age groups. However, the coherence of older participants was characterized by (i) lower magnitude and (ii) mediolaterally broader and more rostrally centered cortical distributions. These characteristics suggest that aging changes how the primary motor cortex participates in the cyclical movements, and such change may extend to walking.